Erosion features of tungsten surfaces under combined steady-state and transient plasma loads - Herashchenko, S.S.; Makhlaj, V.A.; Girka, O.I.; Aksenov, N.N.; Bizyukov, I.A.; Malykhin, S.V.; Surovitskiy, S.V.; Sereda, K.N.; Bizyukov, A.A. (Вопросы атомной науки и техники, 2016)
The paper presents the experimental research on damage of the tungsten surfaces under combined plasma exposures. Steady-state hydrogen exposures (particle flux of 2×10²² m⁻²s⁻¹ , heat flux of 1.7 MW/m² , fluence of 1026 m⁻² , average ion energy of 2 keV) were provided by FALCON ion source. The pulsed plasma loads below the tungsten melting threshold (hydrogen plasma streams with surface heat load of 0.45 MJ/m² and the pulse duration of 0.25 ms) were performed by means of QSPA Kh-50 device. The behavior of structure, sub- structure and stress-state of tungsten samples have been studied after each cycle of pulsed and steady-state plasma loads. Представлено экспериментальное исследование повреждения вольфрамовых поверхностей, подверженных комбинированному плазменному воздействию. Стационарные водородные ионные потоки (поток частиц 2×10²² м⁻² с⁻¹ , тепловой поток 1,7 МВт м⁻² , флюенс 1026 ·м⁻² , средняя энергия ионов 2 кэВ) получены с помощью источника ионов FALCON. Импульсные плазменные нагрузки ниже порога плавления вольфрама (потоки водородной плазмы с удельной энергией 0,45 МДж·м⁻² и длительностью импульса 0,25 мс) создавались на КСПУ Х-50. Изучено изменение структуры, субструктуры и напряженно- деформированного состояния вольфрамовых образцов под влиянием многоцикличных плазменных нагрузок. Представлено експериментальне дослідження пошкодження вольфрамових поверхонь під дією комбінованого плазмовому впливу. Стаціонарні водневі іонні потоки (потік частинок 2×10²² м⁻² с⁻¹, тепловий потік 1,7 МВт·м⁻² , флюенс 1026 м⁻² , середня енергія іонів 2 кеВ) отримані за допомогою джерела іонів FALCON. Імпульсні плазмові навантаження нижче порога плавлення вольфраму (потоки водневої плазми з питомою енергією 0,45 МДж·м⁻² і тривалістю імпульсу 0,25 мс) створювалися на КСПП Х-50. Вивчено зміну структури, субструктури і напружено-деформованого стану вольфрамових зразків під впливом багатоциклічних плазмових навантажень.